2005
DOI: 10.1157/13075950
|View full text |Cite
|
Sign up to set email alerts
|

State size as measured in terms of public spending and world health, 1990-2000

Abstract: The study suggests that state size (in terms of public spending) has an important influence upon health and particularly upon mortality. Although it is important to bear in mind the limitations of this study and the reduced time window used, these results should be taken into consideration in the current political and epidemiological debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…A study which analyzed government spending on health and public health indicators suggested that public health spending had an important influence upon health and particularly upon infant mortality. 1 A study on state health expenditure and IMR in India also showed similar results. 2 High income countries and countries with access to natural resources like oil, spend a greater proportion of their wealth on providing and building a robust health infrastructure.…”
Section: Introductionmentioning
confidence: 62%
“…A study which analyzed government spending on health and public health indicators suggested that public health spending had an important influence upon health and particularly upon infant mortality. 1 A study on state health expenditure and IMR in India also showed similar results. 2 High income countries and countries with access to natural resources like oil, spend a greater proportion of their wealth on providing and building a robust health infrastructure.…”
Section: Introductionmentioning
confidence: 62%
“…One study found that reduced government funding weakened health services, such that responses to HIV/AIDS in Sub-Saharan Africa were significantly impaired [ 59 ]. Empirical studies assessing the effect of health expenditures or government spending more broadly find a significant and detrimental relationship with infant mortality [ 58 , 60 , 61 ], under-5 mortality [ 58 ], and other health outcomes [ 62 ]. IFI-affiliated authors contest the notion that structural adjustment programmes reduce health spending [ 63 ] or claim they are associated with increased spending [ 19 , 20 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%